Earnings and Prices, 1904, 1914, 1937-8 - Bowley, A. L. (Review of Economic Studies, 1941)
Earnings and Prices, 1904, 1914, 1937–8 Get access A. L. Bowley A. L. Bowley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 3, June 1941, Pages 129–142, https://doi.org/10.2307/2967598 Published: 01 June 1941